Research overview of macroscopic thermal contact resistance - WANG Xian-wei; WANG Zhao-liang; HE Qing; LI Xiu-lian (工程科学学报)
Given the limitations of manufacturing precision, manufacturing cost, and other factors, contact clearance is always inevitable at the contact interface of components. The contact clearance leads to the reduction of heat flux during the heat transfer process. The effect of thermal contact resistance is significant, particularly in the fields of aerospace, microelectrical technology, and cryogenic superconductor that are closely related to the operating temperature. The thermal contact resistance is affected by many factors, such as size, shape, space of asperity, mechanical properties of the material, external pressure, and temperature. Moreover, these factors usually interact with each other and need to be coupled. Thus, how to describe the thermal contact resistance accurately and build the appropriate prediction model are the key problems that should be resolved during engineering calculations. On the basis of the research results of domestic and international scholars, the current research state of thermal contact resistance during theoretical calculations and engineering applications were presented. The theoretical calculation, experimental measurement, and digital simulation methods used to analyze macroscopic thermal contact resistance were summarized, and the advantages and disadvantages of these methods were indicated. The effects of different factors on macroscopic thermal contact resistance were briefly discussed. On the basis of the combined cooling experiments of low-temperature superconducting magnet coils of the China Fusion Engineering Test Reactor, the effects of heat flow direction, temperature, and pressure on the thermal contact resistance of superconducting magnet components, such as stainless-steel jacket, dielectric insulation material, and quench protection material, were analyzed. Moreover, the reason why the effects of temperature and external pressure result in the change of thermal contact resistance was investigated from the perspective of thermal mechanics. Finally, given the accuracy and convenience requirements for the calculation of thermal contact resistance during engineering practice, the future research direction was indicated.